In Vitro Kinematics of the Proximal Interphalangeal Joint in the Finger after Progressive Disruption of the Main Supporting Structures. (September 2015) - Caravaggi, Paolo; Shamian, Benhoor; Uko, Linda; Chen, Linda; Melamed, Eitan; Capo, John T.
Background: Fractures and dislocations of the proximal interphalangeal (PIP) joint of the fingers are among the most common causes of injury in the hand. Objective assessment of the kinematic alterations occurring when the supporting structures are disrupted is critical to obtain a more accurate indication of joint stability. Methods: An in vitro cadaver model of the hand was used to evaluate the kinematics of the PIP joint in the finger during active unrestrained flexion and extension. The kinematics of the PIP joint following progressive disruption of the main supporting structures was measured using an optical tracking system and compared with those in the intact joint. Results: Flexion of the intact PIP joint was associated with joint compression, volar displacement, and rotational movements. Release of the main soft-tissue stabilizers and 30 % of volar lip disruption resulted in substantial alteration of several kinematic variables. The normalized maximum dorsal/volar translation was 0.1±1.3 % in the intact group and 14.4± 11.3 % in the injured joint. Conclusions: In the intact PIP joint, rotations and translation are strongly coupled to the amount of joint flexion. Gross instability of the PIP joint occurs when disruption of the collateral ligaments and volar plate is accompanied by resection of at least 30 % of volar lip of the middle phalanx. Collateral ligament injuries, volar plate injuries alone, and fractures at the volar base of the middle phalanx that involve less than 30 % of the articular surface are unlikely to result in gross instability and may be managed effectively with nonoperative treatments.